Accuracy of abbreviated multiparametric MRI-derived protocols in predicting local staging of prostate cancer in men undergoing radical prostatectomy. (July 2021) - Giannarini, Gianluca; Cereser, Lorenzo; Como, Giuseppe; Bonato, Filippo; Pizzolitto, Stefano; Valotto, Claudio; Ficarra, Vincenzo; Dal Moro, Fabrizio; Zuiani, Chiara; Girometti, Rossano
Background: Abbreviated magnetic resonance imaging (aMRI) protocols have emerged as an alternative to multiparametric MRI (mpMRI) to reduce examination time and costs. Purpose: To compare multiple aMRI protocols for predicting pathological stage ≥T3 (≥pT3) prostate cancer (PCa). Material and Methods: One hundred and eight men undergoing staging mpMRI before radical prostatectomy (RP) were retrospectively evaluated. 3.0-T imaging was performed with a 32-channel surface coil and a protocol including diffusion-weighted imaging (DWI), transverse T2-weighted (tT2W) imaging, coronal T2W (cT2W) imaging, sagittal T2W (sT2) imaging, and dynamic contrast-enhanced (DCE) imaging. Two readers independently assessed whether any MRI observation showed stage ≥T3 on each sequence (reading order: DWI, cT2W, tT2W, sT2W, DCE). Final stage was assessed by matching readers' assignments to pathology, and combining them into eight protocols: DWI + tT2W, DWI + cT2W + tT2W, DWI + tT2W + sT2W, DWI + cT2W + tT2W + sT2W, DWI + tT2W + DCE, DWI + cT2W + tT2W + DCE, DWI + tT2W + sT2W + DCE, and mpMRI. Diagnostic accuracy and inter-reader agreement for aMRI protocols were calculated. Results: Prevalence of ≥pT3 PCa was 31.5%. Sensitivity, specificity, positive (PPV) and negative predictive value (NPV) of aMRI protocols were comparable to mpMRI for R1. Sensitivity was 74.3% (95% confidence interval [CI] 64.8–72.0) to 77.1% (95% CI 67.9–84.4), and NPV 86.8% (95% CI 78.6–92.3) to 88.1% (95% CI 80.1–93.3). All accuracy measures of the various aMRI protocols were similar to mpMRI also for R2, albeit all slightly lower compared to R1. On a per-protocol basis, there was substantial inter-reader agreement in predicting stage ≥pT3 (k 0.63–0.67). Conclusion: When comparing the diagnostic accuracy of multiple aMRI protocols against mpMRI for predicting stage ≥pT3 PCa, the protocol with the fewest sequences (DWI + tT2W) is apparently equivalent to standard mpMRI.